2012
DOI: 10.5152/akd.2012.214
|View full text |Cite
|
Sign up to set email alerts
|

Clinical biomarkers of high-density lipoprotein dysfunction among middle-aged Turks

Abstract: Objective: Impaired function of high-density lipoprotein (HDL) particles generates cardiometabolic disorders in people prone to impaired glucose tolerance for which clinical biomarkers need delineation. Study design: Prospective population-based study. Methods: Totally, data of 2725 adults followed-up over 7.3±3.0 years were analyzed by Cox regression analysis. C-reactive protein (CRP), complement C3 (C3), triglycerides (Trg) and HDL-cholesterol were tested to predict risk for incident diabetes or coronary hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…A high TG/HDL ratio alone was predictive of CHD risk only in men, whereas combined presence of high TG/HDL ratio and elevated CRP conferred CHD risk in women. The interplay across gender, hypertriglyceridemia, elevated CRP and HDL dysfunction in the development of cardio metabolic risk sex the joint role of the proinflammatory state, represented by elevated circulating TG, CRP and HDL dysfunction (67) .…”
Section: C-reactive Proteinmentioning
confidence: 99%
“…A high TG/HDL ratio alone was predictive of CHD risk only in men, whereas combined presence of high TG/HDL ratio and elevated CRP conferred CHD risk in women. The interplay across gender, hypertriglyceridemia, elevated CRP and HDL dysfunction in the development of cardio metabolic risk sex the joint role of the proinflammatory state, represented by elevated circulating TG, CRP and HDL dysfunction (67) .…”
Section: C-reactive Proteinmentioning
confidence: 99%
“…[ 6 ] Although numerous prospective and cross-sectional trials have been carried out, there is no agreement about which indicator has a stronger relationship with blood pressure (BP) and which is a stand-alone risk factor. [ 6 , 7 , 8 , 9 , 10 , 11 ] The Prospective Population-Based Turkish Adult Risk Factor Study determined BMI in women and WHR in men as predictors of systolic BP (SBP) and diastolic BP (DBP)[ 12 ] while another study reported that WC was an independent indicator in hypertensive patients. [ 13 ] However, up to date, the efficacy of anthropometric indices as a direct predictor of hypertension and the relationship between BP has not been comprehensively investigated in Turkish adults.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 ] However, up to date, the efficacy of anthropometric indices as a direct predictor of hypertension and the relationship between BP has not been comprehensively investigated in Turkish adults. [ 12 , 13 , 14 ]…”
Section: Introductionmentioning
confidence: 99%
“…10 A limited number of studies exist quantifying the prevalence of HTG in Turkey. [11][12][13] Kayıkçıoğlu et al 13 reported a prevalence of HTG (>150 mg/dL) in Turkey 36.5% in general. Onat A.…”
mentioning
confidence: 99%
“…Onat A. 12 reported a prevalence of mild-to-moderate HTG in Turkey of 39.6% and 29.2% in men and women, respectively, and Bayram et al 11 reported the population prevalence of HTG as 35.7% (33.5% for women and 38.3% for men). Analysis of rare LOF variants in Turkish patients with HTG has not been previously performed.…”
mentioning
confidence: 99%